Systematic Literature Review: Management Information Systems and Information Technology - Putri, Wan Hafizah Ainun Syah; Fadhilah, Ulfa; Lubis, Mhd Muchlisin; Khowarizmi, Al (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
This research aims to review articles related to Management Information Systems with Information Technology. This research method uses SLR (Systematic Literature Review) where article sources are taken from several databases in order to obtain data that matches the title of this article. Data retrieval sources come from searches of national and international journals published on Google Scholar, through the Publish or Perish application. The results of the analysis using VOSviewer on network visualization, overlay visualization, and density visualization show the relationship between various concepts related to management information systems and information technology.